﻿Selaginella densiciliata (subg. Heterostachys, Selaginellaceae), a new spikemoss species from China based on morphological and molecular data - Shao-Li Fang; Bo Xu; Liang Zhang; Zhao-Rong He; Xin-Mao Zhou (PhytoKeys, 2023)
A new species of spikemoss, Selaginella densiciliata in S. subg. Heterostachys sect. Tetragonostachyae, China, is described from southeastern Xizang, based on morphological and molecular phylogenetic data. Morphologically, S. densiciliata is similar to S. repanda, S. subvaginata and S. vaginata, but the new species can be easily distinguished from them by having sterile leaves margins densely ciliate, symmetrical axillary leaves oblong ovate to ovate-triangular, and ovate dorsal leaves obviously carinate. Molecular phylogenetic analysis resolves S. densiciliata as sister to the clade comprised with S. vaginata and S. xipholepis, which confirms the recognition of the new species.